Airway Closure during Surgical Pneumoperitoneum in Obese Patients. (July 2019) - Grieco, Domenico Luca; Anzellotti, Gian Marco; Russo, Andrea; Bongiovanni, Filippo; Costantini, Barbara; D'Indinosante, Marco; Varone, Francesco; Cavallaro, Fabio; Tortorella, Lucia; Polidori, Lorenzo; Romanò, Bruno; Gallotta, Valerio; et al.
Editor's Perspective: What We Already Know about This Topic: Airway closure has been described in chronic obstructive pulmonary disease, acute respiratory distress syndrome, and cardiac arrest patients This phenomenon makes tidal inflation start only after a critical airway opening pressure is overcome Although previously reported during general anesthesia, airway closure was partially misinterpreted What This Article Tells Us That Is New: Airway closure affects a relevant proportion of obese patients undergoing general anesthesia in supine position, with a variable degree of airway opening pressure With Trendelenburg pneumoperitoneum, airway opening pressure increases consistently with esophageal pressure and pneumoperitoneum insufflation pressure: consequently, transalveolar pressure, lung volumes, and alveolar recruitment do not vary Airway closure yields bedside misinterpretation of respiratory mechanics and underestimation of actual alveolar pressure in the intraoperative setting It is an occult phenomenon that generates an airway pressure threshold, whereby inspiratory gas does not inflate the lung unless the airway opening pressure is exceeded Background: Airway closure causes lack of communication between proximal airways and alveoli, making tidal inflation start only after a critical airway opening pressure is overcome. The authors conducted a matched cohort study to report the existence of this phenomenon among obese patients undergoing general anesthesia. Methods: Within the procedures of a clinical trial during gynecological surgery, obese patients underwent respiratory/lung mechanics and lung volume assessment both before and after pneumoperitoneum, in the supine and Trendelenburg positions, respectively. Among patients included in this study, those exhibiting airway closure were compared to a control group of subjects enrolled in the same trial and matched in 1:1 ratio according to body mass index. Results: Eleven of 50 patients (22%) showed airway closure after intubation, with a median (interquartile range) airway opening pressure of 9 cm H2 O (6 to 12). With pneumoperitoneum, airway opening pressure increased up to 21 cm H2 O (19 to 28) and end-expiratory lung volume remained unchanged (1, 294 ml [1, 154 to 1, 363] vs . 1, 160 ml [1, 118 to 1, 256], P = 0.155), because end-expiratory alveolar pressure increased consistently with airway opening pressure and counterbalanced pneumoperitoneum-induced increases in end-expiratory esophageal pressure (16 cm H2 O [15 to 19] vs . 27 cm H2 O [23 to 30], P = 0.005). Conversely, matched control subjects experienced a statistically significant greater reduction in end-expiratory lung volume due to pneumoperitoneum (1, 113 ml [1, 040 to 1, 577] vs . 1, 000 ml [821 to 1, 061], P = 0.006). With airway closure, static/dynamic mechanics failed to measure actual lung/respiratory mechanics. When patients with airway closure underwent pressure-controlled ventilation, no tidal volume was inflated until inspiratory pressure overcame airway opening pressure. Conclusions: In obese patients, complete airway closure is frequent during anesthesia and is worsened by Trendelenburg pneumoperitoneum, which increases airway opening pressure and alveolar pressure: besides preventing alveolar derecruitment, this yields misinterpretation of respiratory mechanics and generates a pressure threshold to inflate the lung that can reach high values, spreading concerns on the safety of pressure-controlled modes in this setting. Abstract : Airway closure affects a relevant proportion of obese patients undergoing general anesthesia in supine position, with a variable degree of airway opening pressure. With Trendelenburg pneumoperitoneum, airway opening pressure increases consistently with esophageal pressure and pneumoperitoneum insufflation pressure: consequently, transalveolar pressure, lung volumes, and alveolar recruitment do not vary. Airway closure yields bedside misinterpretation of respiratory mechanics and underestimation of actual alveolar pressure in the intraoperative setting. It is an occult phenomenon that generates an airway pressure threshold, whereby inspiratory gas does not inflate the lung unless the airway opening pressure is exceeded.